Streptococcus agalactiae colonization and screening approach in high-risk pregnant women in southern Brazil - Jeane Zanini da Rocha; Jéssica Feltraco; Vanessa Radin; Carla Vitola Gonçalves; Pedro Eduardo Almeida da Silva; Andrea von Groll (Journal of Infection in Developing Countries)
Introduction: Considering that Group B Streptococcus (GBS) persists as an important cause of neonatal morbidity and mortality, the objective of this study was to evaluate the frequency of maternal colonization by GBS, comparing the culture by the Granada broth with the GeneXpert real-time PCR diagnostic methods and the impact of chemoprophylaxis in high-risk pregnant women.